Navigating the Disinformation Maze: A Bibliometric Analysis of Scholarly Efforts - George-Cristian Tătaru; Adrian Domenteanu; Camelia Delcea; Margareta Stela Florescu; Mihai Orzan; Liviu-Adrian Cotfas (Information, 2024)
The increasing prevalence of disinformation has become a global challenge, exacerbated by the rapid dissemination of information in online environments. The present study conducts a bibliometric analysis of scholarly efforts made over time in the research papers associated with the disinformation field. Thus, this paper aims to understand and help combat disinformation by focusing on methodologies, datasets, and key metadata. Through a bibliometric approach, the study identifies leading authors, affiliations, and journals and examines collaboration networks in the field of disinformation. This analysis highlights the significant growth in research on disinformation, particularly in response to events such as the 2016 U.S. election, Brexit, and the COVID-19 pandemic, with an overall growth rate of 15.14% in the entire analyzed period. The results of the analysis underscore the role of social media and artificial intelligence in the spread of disinformation, as well as the importance of fact-checking technologies. Findings reveal that the most prolific contributions come from universities in the United States of America (USA), the United Kingdom (UK), Spain, and other global institutions, with a notable increase in publications since 2018. Through thematic maps, a keyword analysis, and collaboration networks, this study provides a comprehensive overview of the evolving field of disinformation research, offering valuable insights for future investigations and policy development.